The State Financial System as a Main Element of Implementing Regional Government in The Unitary State - Mas Iman Kusnandar; Refi Pratiwi (Journal of Applied Business, Taxation and Economics Research, 2021)
The basis and objectives of the state are contained in the Constitution as stated in the Preambule of the 1945 Constitution of the Republic of Indonesia To make it happen, it is necessary, among others, to support an integrated budgeting system through fiscal policy, so it can be formulated, First, how to realize the correlation of budget principles to the planning system which includes programs and activities of local governments. Second, why is regional financial management a subsystem of the state financial system, and the main elements of local government administration. This study is a qualitative research method through a normative juridical approach and empirical analysis. Research result; First, the Regional Revenue and Expenditure Budget is an integrated budgeting principle that is integrated with the regional government planning system; Second, the success of local government administration is largely determined by an integrated system in the management of regional finances as a subsystem of state finance in the form of a unitary state.